(untitled) (Journal of the College of Basic Education, 2023)
The image of women was embodied in plastic art throughout the stages of history and eras in different forms and forms, as she had a tangible and clear presence throughout the ages, as she represented many aspects of her daily life, as in addition to being responsible for the affairs of the house and children, she contributed to the work of agriculture, knitting and pottery . And she embodied roles in which one differs from the other in terms of their connotations and meanings in their urban and rural aspects, because of the great role of women in society since time immemorial, as they represent half of society, as they are the mother, sister, wife, and lover, in addition to her role in life alongside the man, supporting him, helping him, supporting him, and helping him in the conditions of life. It is not permissible for us to deny her this role and this right. Every work of art carries within it an idea that is intended to be communicated by the artist to the recipient, so we must know the meaning of women in painting in general and Iraqi painting in particular. Most of the artists dealt with women in many of their works, so the researcher decided in this subject of her research to study the role of women in plastic painting and the most prominent and important contents that were mentioned in a selected group of the works of the artist Saad Al-Taie and at different stages and different environments in Iraqi art.